Genetic mapping of white mold related traits using Pinto bean RIL populations derived from the USDA-ARS Bean Program - Lopes, Fernanda Souza (2021)
White mold disease caused by the fungus Sclerotinia sclerotiorum has limited the high productivity of the bean, causing significant losses. The best way to control this disease is to use cultivars with some level of genetic resistance. The first work was carried out with the objective of phenotyping and genotyping an F5:6 pinto bean RIL population with 164 lines from the crossing of PT12-37xVCP-13 in the greenhouse for physiological reaction to white mold using the straw test method. In this method, an agar disk with mycelium of the grown fungus was inserted into the main stem of the plant 21-28 days after sowing with the aid of micropipette tips, and seven, twelve, and sixteen dpi, the evaluation was carried out by a diagrammatic scoring scale. Simultaneously with phenotyping, genomic DNA was extracted and quantified. DNA samples were added to the plates and sent to be genotyped on a BeadChip (Illumina BARCBean6K) containing ~5,398 SNPs. In this mapping, the P. vulgaris reference genome G19833 v2.1 was used to align the generated SNPs. A Chi-square test for segregation ratio was performed and significant deviation from expected Mendelian segregation ratio or SNP markers with >20% missing data were removed. Redundant SNP markers showing complete linkage (100%) were filtered out during linkage map construction. The population linkage map was developed by the MapDisto program and analyzed for QTL using R/QTL. The QTL analysis revealed one major QTL on Pv05 (34%) and two smaller QTLs on Pv04 (6%) and Pv09 (5%) seven dpi. The WM5.4 QTL found in this study corresponds to the WM5.4 meta-QTL previously described. Resequencing data were used to find SNPs present in P. coccineus (G35346). Three markers (C05_34901413, C05_34927709, and C05_35044557) were developed for WM5.4 QTL and amplified in the P3/VCP population, and two of these markers (C05_34901413, C05_34927709) can be used for marker-assisted selection (MAS). The second study was carried out with the objective of phenotyping and genotyping the F5:6 pinto bean RIL population with 196 lines from the cross between PT9-5-6/USPT-WM-12 in greenhouse and field for reaction to white mold, and for lodging and maturity in the field. The same methodology for phenotyping and genotyping was used in this second population except the Illumina BARCBean12K BeadChip with ~12,000 SNP markers was used. Three QTL for physiological resistance were identified by the straw test: WM1.2 with 11% phenotypic variance explained, WM7.4 (19%), and WM11.1 (11%). QTL WM11.1 showed epistatic interaction with WM1.2. Two QTL for lodging resistance and two for maturity were observed. LDG7.1, LDG11.1, MAT2.1 and MAT3.1 presented 40.69%, 12.15%, 46.94%, 10.32%, of the phenotypic variance explained, respectively. The new (and some validated) QTL, both for agronomic traits (lodging and maturity) and for white mold resistance in greenhouse and field, provide new information for breeders to generate white mold resistant bean cultivars with better agronomic traits.